Application of enzyme preparation in alcoholic industry / Wang Sihan, Li Jing and Song Leyi - Wang, Sihan; Li, Jing; Song, Leyi (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The use of enzymes in industrial production has increased greatly, especially in the alcoholic industry, namely beer, grape wine, Huang jiu, and liquors. Diacetyl produced in the fermentation process of beer affect the essence of beer in which α-acetyllactate decarboxylase plays a good inhibitory role. Glucosidase, pectinase, and lysozyme play their respective roles in the process of grape wine fermentation. Huang jiu is produced through traditional technology by taking glutinous rice and japonica rice as the main raw materials and employing wheat koji or a variety of microorganisms contained in rice koji. Wheat koji provides rich enzyme systems such as amylase and protease for the brewing process of rice wine. Enzymes are widely used in various stages of liquor production, such as making koji, fermentation of grains, distillation blending, and waste utilization of distillers' grains. This paper mainly describes the application of enzymes in the production of various wine industries, the improvement of enzyme stability through enzyme immobilization, the treatment of waste enzymes in the wine making process and the future challenges and development.